The right to basic sanitation: land use and water quality after decommissioning of a landfill in Arantina, Minas Gerais, Brazil - Garrido, Fabiola de Sampaio Rodrigues Grazinoli; Oliveira, Valéria Garcez de (Ciência e Natura, 2019)
Arantina, a municipality of Minas Gerais, Brazil, has 2,873 inhabitants by 2010 IBGE census. It does not have a water treatment system and, until 2017, water was distributed directly from the catchment area to residential areas. The water catchment area was located downstream of a landfill that was decommissioned in 2013 and was not subjected to health risk assessment. The objective of this study was to report the land use conditions of this contaminated area located upstream of a water damn and the quality of the water from the damn - pH and electrical conductivity - were analyzed in water samples collected from the catchment area, residential areas, and water mines used as water sources by the residents. In addition, the analysis of official data on the health of the residents indicates the need to invest in basic sanitation.